2007
DOI: 10.1080/07481180600985041
|View full text |Cite
|
Sign up to set email alerts
|

Relatives' Perspective on the Terminally Ill Patients Who Died after Euthanasia or Physician-Assisted Suicide: A Retrospective Cross-Sectional Interview Study in the Netherlands

Abstract: This study used retrospective interviews with 87 relatives to describe the experiences of patients who died by euthanasia or physician-assisted suicide (EAS) in the Netherlands. Most of the patients suffered from cancer (85%). The relatives were most often a partner (63%) or a child (28%) of the patient. Before explicitly requesting EAS most patients (79%) had spoken about their wishes concerning medical end-of-life decisions to be made at a later date. Hopeless suffering, loss of dignity, and no prospect of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 19 publications
1
45
0
Order By: Relevance
“…Sixteen qualitative studies met our inclusion criteria. [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] The characteristics of these studies are described in Table 2; quality assessment is detailed in Table 3. We found all 16 studies to be of good or moderately good quality.…”
Section: Summary Of Included Qualitative Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Sixteen qualitative studies met our inclusion criteria. [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] The characteristics of these studies are described in Table 2; quality assessment is detailed in Table 3. We found all 16 studies to be of good or moderately good quality.…”
Section: Summary Of Included Qualitative Studiesmentioning
confidence: 99%
“…25 Three studies reported the views of people who were pursuing assisted dying or the relatives of those who had been helped to end their lives. 26,30,36 In one study, the participants were described as 'vulnerable' women (elderly, homeless, victims of violence or non-English-speaking minority). 35 and in another, they were older women of orthodox Jewish faith.…”
Section: Summary Of Included Qualitative Studiesmentioning
confidence: 99%
“…A sizeable majority of the research published on this topic corresponds to retrospective studies which analyse data collected from indirect sources: health professionals or informal caregivers and relatives of patients who have expressed a WTHD [65,66]. With regard to prospective studies, they can be classified according to one of two methodological approaches.…”
Section: Epidemiology Of the Wthd And Instruments For Measuring Itmentioning
confidence: 99%
“…In the Netherlands 5–25% of people whose requests for euthanasia/PASwere granted had depression ‘to a great or very great extent’23 (not formally defined) or as a ‘motivating factor’ in their request 24. 11–23% of amyotrophic lateral sclerosis (ALS) patients were usinganti-depressants or showed specific depressive symptoms (anhedonia,depressed mood and feelings of guilt) in the end-stage of disease 25.…”
Section: Resultsmentioning
confidence: 99%
“…In the Netherlands, where euthanasia and PAS are legal, high-quality studies showed a depression rate of 2–10% in euthanasia/PAS cases 16–20 23 24. There is convincing evidence to show that depression is a significant factor in refusing euthanasia/PAS requests,16 18–20 with supporting high- and medium-quality evidence showing that the rate of depression in completed euthanasia/PAS cases is no different from the surrounding population of seriously ill patients 16 17 25.…”
Section: Discussionmentioning
confidence: 99%